Pengaruh Persepsi, Motivasi, Pengetahuan Perpajakan Terhadap Pilihan Berkarir Sebagai Konsultan Pajak: (Studi Kasus Pada Mahasiswa Akuntansi Universitas Hindu Indonesia) - Suartini, Ni Made; I Wayan Sudiana; Kadek Dewi Padnyawati (UNHI Press, 2025)
Careers in taxation have great opportunities for accounting graduates, especially as tax consultants, because the profession is still very much needed. In choosing a tax consultant can be influenced by many factors such as perception, motivation and taxation knowledge. This study aims in this study to determine the effect of perception, motivation and knowledge of taxation on student interest in a career as a public accountant. The population in the study were students of the Accounting Department of Hindu University of Indonesia who had taken taxation courses with the sample used, namely 196 respondents. The research method used is quantitative. The data analysis technique used in this study is multiple linear regression, the coefficient of determination, the F test and the t test. Based on the results of the study, it can be seen that perception has a positive and significant effect on student interest in a career as a public accountant, where a regression coefficient of 0.316 and sig 0.001 is obtained. (2) motivation has a positive and significant effect on student interest in a career as a public accountant, where a regression coefficient of 0.314 and sig 0.000 is obtained. (3) taxation knowledge has a positive and significant effect on student interest in a career as a public accountant, where a regression coefficient of 0.242 and sig 0.000 is obtained. The magnitude of the influence of the independent variables on student interest in a career as a public accountant is 59.3%.